2013
DOI: 10.3109/14767058.2013.855893
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal invasive testing: a 13-year single institution experience

Abstract: Changes in our national prenatal policy through this 13-year period show an increasing efficiency of prenatal detection of CA. However, despite the intensifying screening policies, low-risk pregnant women show a growing demand for prenatal invasive testing and a baseline risk for cytogenetic abnormality of 1/241.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…Type and rate of numerical or structural chromosomal abnormalities found were similar to that of several previous studies [ 25 , 26 ]. Numerical anomalies were found in twenty cases and included ten trisomy 21, four trisomy 18, four monosomies X, one trisomy 20 and one triploidy.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Type and rate of numerical or structural chromosomal abnormalities found were similar to that of several previous studies [ 25 , 26 ]. Numerical anomalies were found in twenty cases and included ten trisomy 21, four trisomy 18, four monosomies X, one trisomy 20 and one triploidy.…”
Section: Resultssupporting
confidence: 90%
“…In the period under study, average maternal age of our population, at pregnancy, increased from 27 to 32 years [ 23 ]. AMA has currently been dropped as indication for invasive PND; nevertheless, maternal age was our main referral until 1997 and according to published studies it is the only etiological factor that correlates with frequency of aneuploidies [ 25 ]. Among the 28 chromosomal abnormalities and the 81 monogenic disorders detected, comparison of maternal age at sampling revealed that similar results were observed in the two groups and both are below what was considered advanced maternal age (cut-off 35 years), indicating an a priori low risk population ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed a steady decline in PNDx after the introduction of FTS in 2000, in keeping with the global experience of this screening test. 7,26,27 The introduction of cfDNAbased screening in 2013 coincided with an unprecedented annual drop in invasive testing, suggesting a substantial impact of this technology as observed elsewhere. [7][8][9] The total number of prenatal diagnoses of trisomy 21 in Victoria more than doubled over the same period, providing evidence that the decline in invasive testing was not at the expense of reduced detection.…”
Section: Discussionmentioning
confidence: 92%
“…Miscarriage, transient amniotic fluid leakage, fetal injury and intrauterine infection may occur [7,12,20]. It has to be emphasized that all forms of prenatal testing must be voluntary [21,22]. Zdr Publ 2015;125 (1) The most common indications for the procedure were: advanced maternal age -86 (36.2% of cases), improper ultrasound scan -71 patients (29.8%), improper biochemical screening tests -77 patients (32.6%) history of a child with a chromosomal abnormality -13 (5.7%).…”
Section: Resultsmentioning
confidence: 99%